Defining and developing expertise in tracheal intubation using a GlideScope® for anaesthetists with expertise in Macintosh direct laryngoscopy: an in‐vivo longitudinal study. (1st October 2014) - Cortellazzi, P.; Caldiroli, D.; Byrne, A.; Sommariva, A.; Orena, E. F.; Tramacere, I.
Summary Although videolaryngoscopy can provide excellent views of the laryngeal structures as both the primary method of tracheal intubation and as a rescue technique for difficult direct laryngoscopy, the existing literature is inadequate to define expertise or even competence. We observed the performance of nine trainees during 890 intubations, with an additional 72 intubations performed by expert anaesthetists used as a control group. Univariate and multivariate mixed‐effects logistic regression models were applied to detect potential predictors of successful intubation and define the number of intubations necessary for a trainee to achieve expertise (> 90% probability of optimal performance). Optimal performance was predicted by single laryngoscope insertion (p < 0.001) and a Cormack and Lehane grade‐1 view (p < 0.001), and not by normal lifting force applied to the device (p = 0.15), with expertise reached after 76 attempts. These results indicate that expertise in videolaryngoscopy requires prolonged training and practice.